RCS of Chiral Elliptic Cylinder Embedded in Infinite Chiral Medium - A-K. Hamid; W. Obaid (Institute of Advanced Engineering and Science, 2017)
This paper presents an analytic solution to the scattering properties of chiral elliptic cylinder embedded in infinite chiral medium due to incident plane wave. The external electromagnetic fields as well as the internal electromagnetic fields are written in terms Mathieu functions and expansion coefficients. In order to obtain both the internal and external unknown field expansion coefficients, the boundary conditions are applied rigorously at the surface of different chiral/chiral material. Results are plotted graphically for the normalized scattering widths for elliptic cylinders of different sizes and chiral materials to show the effects of these parameters on scattering cross widths. It is shown numerically by adding the external chiral material to elliptic cylinder provides more parameters to control the RCS.